Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada PT Akasha Wira Internasional Tbk Periode 2022-2023 - Dini Dwi Lestari; Dwi Puji Kusrahayu; M. Thoha Ainun Najib (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
This research was conducted at PT Akasha Wira Internasional Tbk, the aim of this research was to determine financial ratio analysis to assess financial performance at PT Akasha Wira Internasional Tbk for the 2022-2023 period. The data collection method used in this research is to obtain information by looking at the data contained in financial report data and by using literature to obtain secondary data, references. The data analysis technique was carried out by comparing the financial ratios at PT Akasha Wira Internasional Tbk with the industry average for companies operating in similar fields. The results of this research state that the financial performance of PT Akasha Wira Internasional in 2022-223, if seen from the liquidity ratio, the company's financial condition is healthy, the solvency ratio shows that the company has a stable funding structure, the activity ratio shows that the company has several areas that require improvement. in operational efficiency, and finally the company's profitability ratio for 2022-2023 shows that the company is facing significant challenges in terms of profitability.